The Lauḥ Method in Early Childhood Qur’anic Pedagogy: A Case Study on Memorization Strategies at Zawiyah Asmariyah, Libya - Taufik Awan Wibowo; Fiqi Restu Subekti (Journal of Early Childhood Education Perspectives, 2026)
This study aims to analyze the Lauḥ method as a pedagogical approach in Qur’anic memorization learning for early childhood learners. The study explicitly situates the analysis within the framework of Early Childhood Education and emphasizes the alignment of the Lauḥ method with children’s developmental characteristics, particularly in cognitive processes, memory, attention, and multisensory learning. The research employs a qualitative approach with a case study design conducted at Zawiyah Asmariyah, Libya. Data were collected through participatory observation, semi-structured interviews with Qur’anic memorization teachers and institutional administrators, and document analysis. The study analyzes the data thematically by linking empirical findings to pedagogical principles of early childhood education. The findings indicate that the Lauḥ method, through stages of preparation, writing, repetition, erasure, and gradual evaluation, aligns with core principles of early childhood learning, including cognitive load management, teacher scaffolding, and the use of visual, auditory, and kinesthetic stimulation. The method contributes to improving children’s focus, memory retention, and learning engagement. The study concludes that the Lauḥ method can function as a relevant and contextual pedagogical approach in Qur’anic memorization learning for early childhood learners when implemented systematically and oriented toward developmental needs.